Territorial capital and the economic crisis: The role of spatial effects - Iolanda Lo Cascio; Fabio Mazzola; Giuseppe Di Giacomo; Rosalia Epifanio (European Regional Science Association (ERSA), 2013)
Activity-geospatial approach forms methodological basis of the concept of geospatial self-organization of a society as new theoretical paradigm of societal geography (SG) with next main principles: a) Self-organization of society and its key subsystems (economical, social, political, spiritual) in specifically localised natural and societal qualities of geospace (Earth's surface space) forms the process of geospatial self-organization of a society and its results - geospatial interests, processes, systems, structures as societal-geospatial phenomena of different scale (global, regional, local, etc.). So societal processes acquire specific geospatial shapes that combine a geospatial (geographic) picture of societal development; b) 'societal-geospaitial relation' is an abstract expression of the content of this picture and forms main theoretical principle of SG; c) geospatial self-organization of a society with different forms of societal-geospatial relations (geoeconomical, geopolitical, geosocial, geospiritual and integrative) is the subject of SG and its different branches. From this perspective, the regional self-organization of society is the subject of regional SG, and a region is a societal-geospatial system, geospatial community of subjects which have the functional unity - economic, social, political, spiritual or integral. This system is the result of the regionalization process: self-organization of society in a particular part of geospace. It depends on specific historical factors, qualities of geospace, geographical position. Factors of regionalization are the processes, which complicate the geospace and creates regions of appropriate type: a) functional - geopolitical, geo-economic, geo-social, geo-spiritual (religious, ethnic, cultural, etc.), b) integral (combine multiple functions) - geoformational (by types of societies - pre-capitalist, capitalist, socialist, etc.), geocivilizational (by civilizational differences), etc., c) processes of integration (globalization, uniting of countries and the administrative units within them, etc.) and disintegration (colonial division of the world, the collapse of the USSR, etc.). On geospatial scale regions can be classified into macro- (Eastern Europe, Central Asia, international regional organizations), meso- (federal districts and subjectes of the Federation in Russia, economical and political regions of countries) and micro- ('euro-regions', administrative districts, communes, etc.). By type regionalization processes and regions are divided into international and internal (with subspecies: functional and integral). Internal regionalization acts as territorial differentiation of political, social, economic and spiritual (cultural, etc.) development of society. By organizational forms of regionalization (depending on the degree of administrative function and legal status) it is possible to define regions as 'de-facto' (historically formed civilizations, ethnocultural regions, etc.) and regions 'de-jure' (administrative units, international regional organizations, etc.).
Keywords: 330